Restoration of load-bearing structures in a multi-storey residential building after a fire caused by military operations - Kramarchuk, Andrii; Ilnytskyy, Borys; Lytvyniak, Oksana (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
This article presents the visual and instrumental investigations, along with the necessary engineering and technical decisions, for restoring load-bearing structures of multi-storey residential buildings damaged by fire due to war. It is economically advisable to replace and strengthen 20% of the emergency floor slabs and 16% of the load-bearing walls to allow residents to return to their homes as soon as possible. The temperature during the fire was determined using specific samples of damaged materials, building structures, and equipment, which allowed for a more accurate assessment of the damage to brick walls and prefabricated reinforced concrete floor slabs. The possibility of further use of the building was also determined based on a survey and necessary measurements of its structures, including the determination of physical and mechanical characteristics (crack width, flexures, concrete strength, brick grade, and mortar grade). The prefabricated reinforced concrete round hollow floor slabs had delaminated along the ribs between the hollows, showing sagging. The bricks had changed colour and were destroyed to a depth of 120 mm (internal walls were destroyed to this depth on both sides). Considering the extent of the damage to the load-bearing structures, it is recommended that the inter-floor ceilings, load-bearing walls, and partitions be replaced and strengthened. For structures that do not require replacement or reinforcement, the justification for their continued safe operation has been completed in accordance with the construction standards and regulations in force in Ukraine.